Exchange curve-based inventory policy analysis of non-reusable industrial packaging in production - Bányainé Tóth, Ágota (Journal of Production Engineering, 2021)
The well-chosen inventory policy has a great impact on the performance of production and logistics processes, because it can influence not only the reliability, the cost efficiency, and the sustainability of the processes and resources, but packaging system can force the quality of products and processes. Within the frame of this article an exchange curve-based analysis method of packaging related inventory policy is described. This analysis method makes it possible to highlight the problems in inventory policy and find an improve solution in both macro and micro-level. The computation method is based on the exchange of annual order cost and average inventory investment, especially in the case of economic order quantity-based packaging order policies.